Effect of Nitrogen on Nitrogenase Activity of Diazotrophs and Total Bacterial Population in Rice Soil - N. Ayuni; O. Radziah; U. A. A. Naher; Q.A. Panhwar; M. S. Halimi (Journal of Animal and Plant Sciences, 2015)
Nitrogen (N) is the most limiting nutrient for rice and thisinput is required in the largest quantity for rice production. Laboratory and glasshouse studies were conducted at Universiti Putra Malaysiato determine the effect of urea-N on diazotrophs (Stenotrophomonas maltophila) growth and colonization on the rice roots and the effect of inoculation on bacterial population. Stenotrophomonas maltophila was grown under laboratory condition and applied with five levels of nitrogen in the form of urea (urea-N) (0, 50, 100, 200 and 300 mg L-1). The same treatments were given to rice plants under glasshouse condition for growth performance effect. Results showed that application of urea-N significantly influenced the population and nitrogenase activity of Stenotrophomonas maltophila. Nitrogenase activity was reduced with increased of urea-N application. The bacteria showed highest acetylene reduction assay (ARA) value of 0.042 µmol C2H4 h-1 mL-1 at 0 mg L-1 urea-N and the ARA was totally inhibited at 300 mg L-1 urea-N. In glasshouse study, the rhizosphere population was reduced by 7.6% with addition of 50 kgha-1, and endosphere population was reduced by 8% with addition of 200 kgha-1 of urea-N. However, photosynthesis and plant biomass were significantly increased by inoculation without affecting the non-rhizosphere population. In general high application of N negatively affected the nitrogenase activity, diazotrophs colonization on rice roots, photosynthesis and plant growth.
Keywords: Acetylene reduction assay; diazotrophs; growth; photosynthesis; plant biomass; Stenotrophomonas maltophila